Icu nurses attitude to evidence based practice in Ardebil University of Medical Science’s hospitalsin1391 - Zolriasatein, fereshteh; Parvindarabad, farahvash; Abedsaeedi, zhila; Baqestani, ahmad reza (Advances in Nursing & Midwifery, 2014)
Abstract Background and aim: The evidence-based practice is the main objective of policy, management and training of health care in developed countries and significant investment has been done to develop it. Cause of high quality care providing importance in the ICU, it is necessary to familiarize nurses with the evidence in care. Awareness of nurse’s attitude allows changing and improving their approach. This study aimed to determine attitudes of nurses working in educational medical science hospitals ICUs in Ardabil city. Materials and methods: In this descriptive study, 234 ICU nurses have selected with census method. To measure the attitude,questionnaire form that its validity was determined by content validity and its reliability was determined by using Cronbach’s alpha(α = 0. 78) have used. Data analysis was performed with the software spss18. Results: Most nurseshad positive attitudes toevidence-basedcaresandevidencevalidityand its useinclinicalcareandnegativeattitudestotheimportanceofcilinicalexperience. There is a significant relation between level of education, clinical experience, training and management, survey quantity, access to result of research, with mean of attitude score. Conclusions: Despite positive attitudes to evidence-based practice and its clinical use, access to research evidence and use is low. Keywords: Evidence based practice, Attitud, ICU, Nurse REFERENCES Aghahoseini SH (2011) [Nurses ‘knowledge and attitude in evidence-based nursing in kashan university of medical sciences’ teaching hospitals]. Tabriz Nursing & Midwifery Journal . 6(2) 45-54 (Persian) Beyea SC ,Slattery M j(2006) Evidence-based Practice in Nursing: A Guide to Successful Implementation Hcpro, Inc. Breimaier H E , Halfens RJG M, Lohrmann C (2010) Nurses’ wishes, knowledge, attitudes and perceived barriers on implementing research findings into practice among graduate nurses in Austria. Journal of Clinical Nursing . 20(11-12)1744-56 Brown CE , Kim sc, Stichler JF,Fields W (2010) Predictors of knowledge, attitudes,use and future use of evidence- based practice among baccalaureate nursing students at two universities. Nurse Education Today . 30(6) 521-527 Bucknal TK (2003) The clinical landscape of critical care: nurses , decision – making Journal of Advanced Nursing. 43(3)310-319 Camiah S (1997) Utilization of nursing research in practice and application strategies to raise research awerness among nurse practitioner: a model for success. Journal of Advanced Nursing. 26(1)193-202 Courtney M (2005) Evidence for Nursing Practice. Elsevier Australia. Cullum N, Ciliska D,Haynes B, Marks S(2010) [Evidence-Based Nursing: An Introduction]. Translated by: SedaqatiM,Hamedi S. 1rst Edition. Tehran. Salemi Publisher. (Persian). Egerod I, Hansen G M. (2004) Evidence-based practice among Danish cardiac nurses: a national survey. Journal of Advanced Nursing. 51(5) 465–473 Estrabrooks C. A (1998) Will evidence based practice make practice perfect? Canadian Journal of Nursing Research. 30(1) 15-36 HabibiSh, RezaeiHachesoo P, Tabaghi R (2010) [ Enhancing information literacy as a base of developing evidence-based nursing]. Health Information Management. 7(3) 371-378)Persian) Hockenbery M, Wilson D, Barrera P (2006) Implementing evidence based nursing practice in a pediatric hospital. Pediatric Nursing. 32(4)371-377 JalaliniaF. The consequences of qualitative and quantitative evidence-based education in nursing students: a study of the combination. The Ph. D. thesis in nursing. Baqiyatallah university of medical sciences. (2011))Persian) KermanshahiS , Parvinian A M (2012) [Barriers to implementation of evidence-based care: Viewpoints of nursing staff]. Iranian Journal of Medical Education. 12(2): 84-92)Persian) Killen M B, Barnfather J S (2005) A successful teaching strategy for applying evidence based practice. Nurse Educator. 30(3) 127-132 Koessl B D. (2009). Factors Influencing Rural Nurses Attitudes and Beliefs Toward Evidence Based Practice,. A thesis submitted in partial fulfillment of the requirements for the degree of Master of Nursing. Montana State University. Koehn M , Lehman K (2008) Nurses perceptions of evidence based nursing practice. Journal of Advanced Nursing. 62(2) 215-209 Koivunen M, Valimaki M ,Hatonenn H (2010) Nurses’ information retrieval skills in psychiatric hospitals– Are the requirements for evidence – based practice fulfilled ? Nurse Education in Practice. 10(1)27-31 Kothari A, Birch S, Charles C (2005) “Interaction” and research utilization in health policies and programs: Does it work? Health Policy. 71(1) 117–125 Krugman M (2003) Evidence – based practice: The role of staff development. Journal for Nurses in Staff Development. 19(6) 279-285 Lai NM , Teng CL, lee ML (2010) The place and barriers of evidence based practice: knowledge and perceptions of medical , nursing and allied health practitioners in malaysia. BMC Research Notes. 3: 279 MehrdadN , Salsali M, Kazemnejad A (2007) [Nurses’ attitudes toward research utilization in clinical practice]. Hayat. 13(2): 41-52)Persian) NezamzadehM,Nouri J Khademolhosseini SM(2011)[ Quality of nursing evidence based guidelines from the nurses view]. Iranian Journal of Critical care Nursing. 4(1)53-58)Persian) O’Donnell CA(2004) Attitudes and knowledge of primary care professionals towards evidence-based practice: a postal survey. Journal of Evaluating Clinical Practice. 10(3) 197-205. Polit D F, Beck C T (2008) Nursing Research: Generating and Assessing Evidence for Nursing Practice. 8nd Edition. Lippincott Williams and Wilkins. Rodgers S (1994) An exploratory study of research utilization by nurses in general medical and surgical wards. Journal of Advanced Nursing. 20(4) 904-911 Rycroft – Malone J et al (2004) An exploration of the factors that influence the implementation of evidence in to practice. Journal of Clinical Nursing 13(8) 913-924 Smith R (1996) What cilinical information do doctors need? British Medical Journal. 313(7064) 1068-1062 Soltani A (2007)[Evidence Based Medicine]. 1rst Edition. Tehran. Tehran university publisher. )Persian) Tahmasebifard N, Nakhshab M, Shafiei M (2012)[A primary study on the attitude, knowledge and behavior of speech and language pathologists toward evidence-based practice]. Journal of Research In Rehabilitation Sciences. 8(1) 65-76)Persian) Wallin L , Bostrom AM , Wikblad K , Edwald U (2003) Sustainability in changing clinical practice promotes evidence-based nursing care. Journal of Advanced Nursing. 41(5) 509-518